Cryopreservation of Allium tuberosum Rottler ex Sprengel - Chander, Subhash; Gowthami, Ravi; Pandey, Ruchira; Agrawal, Anuradha (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):301